Designing,Implementing and Evaluating the Training Sessions of the Reading Club for Undergraduate Students in Audiology - Parisa Heidari; Ghassem Mohammd Khani; Farzaneh Fatahi; Nematollah Rouhbakhsh; Sara Heidari (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Due to the importance of reading reference books in learning and fully understanding academic concepts, this study aimed to assess the changes in the knowledge level of undergraduate audiology students at Tehran University of Medical Sciences, Iran, through book reading sessions. Methods: In this developmental study, book reading sessions were designed and implemented based on the five-stage Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Three chapters from the Handbook of Clinical Audiology were studied over eight two-hour weekly sessions on the Skyroom platform. A knowledge assessment questionnaire was completed by students before and after each chapter. Additionally, students filled out a satisfaction form at the end of each session. Data analysis was performed using descriptive statistics and the Wilcoxon test. Results: Ten out of 22 fifth-semester Undergraduate Students in Audiology participated in the present study. A comparison of students' pre- and post-session scores using the Wilcoxon test indicated a significant difference in their scores for all three chapters studied: Chapter One (P=0.005), Chapter Two (P=0.004), and Chapter Three (P=0.004). The mean difference in students' knowledge scores (out of 5 points) before and after the reading sessions was 2.9, 3.2, and 3.5 for the first, second, and third chapters, respectively. The overall mean satisfaction score for the book reading sessions was 4.7±0.48 out of 5. Conclusion: The present study demonstrated that book reading sessions significantly enhanced students' foundational knowledge of the topics covered in all three chapters of the audiology reference book. Additionally, students expressed a high level of satisfaction with these sessions. Therefore, this method can encourage students to read reference books.